Equity market timing and capital structure: International evidence - Mahajan, Arvind; Tartaroglu, Semih (Journal of Banking & Finance, 2008)
We investigate the equity market timing hypothesis of capital structure in major industrialized (G-7) countries. As claimed by its proponents, we find that leverage of firms is negatively related to the historical market-to-book ratio in all G-7 countries. However, this negative relationship cannot be attributed to equity market timing. We find no association between equity issues and market-to-book ratios at the time of equity financing decisions by Japanese firms. Firms in all G-7 countries, except Japan, undo the effect of equity issuance and the impact of equity market timing attempts on leverage is short lived. This is inconsistent with the prediction of the equity market timing hypothesis and more in line with dynamic trade-off model.